2021
DOI: 10.21608/jcbr.2021.46401.1081
|View full text |Cite
|
Sign up to set email alerts
|

Role of expression of p53 and Ki67 in the progression of Wilms tumor; correlation with survival

Abstract: It is with great pleasure that I write this editorial to welcome you to the IJCBR. This journal provides a platform for publication of original and reviews research articles, short communications, letter to editor, thesis abstract, conference report, and case studies. These types of publication are directed at the interface of the fields of cancer and biomedical research.The IJCBR relies on a distinguished expert of the Advisory and Editorial Board Members from the top international league covering in depth th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…This could also be attributed to the dominant mixed-type histology in our study compared to the blastemal component in these studies where p53 is mostly expressed. 15–17 The number of anaplastic tumors positive for p53 was lower than 76.2% reported in a study by Hill 27 which can be attributed to the large sample size of tumors known to have anaplasia recruited in this study. The difference can be explained by the fact that Hill et al recruited nephrectomy and trucut specimens that had not received preoperative chemotherapy as opposed to our study where most samples were after preoperative chemotherapy.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…This could also be attributed to the dominant mixed-type histology in our study compared to the blastemal component in these studies where p53 is mostly expressed. 15–17 The number of anaplastic tumors positive for p53 was lower than 76.2% reported in a study by Hill 27 which can be attributed to the large sample size of tumors known to have anaplasia recruited in this study. The difference can be explained by the fact that Hill et al recruited nephrectomy and trucut specimens that had not received preoperative chemotherapy as opposed to our study where most samples were after preoperative chemotherapy.…”
Section: Discussioncontrasting
confidence: 62%
“…The expression of p53, however, was lower than 60.3%, and 56% from Egypt and 40% from Kenya. 15,17,21 A study by Salama recruited only nephrectomy specimens and would only include a specimen with at least 4 representative slides, as opposed to our study where even trucut biopsies were recruited which could have affected tumor The expression of WT1 is lower than 66.7% reported in the study done at Osaka University in Japan and 100% by Murphy. 21,25 The difference can be attributed to the different clone 6F-H2 anti-rabbit antibody used as opposed to our CAN-R9 IHC-56-2, while a study by Murphy recruited only blocks for 21 patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…For immunohistochemical studies, in the present study, PHZ showed high positivity for ki67 and p53 in colon cancer tissue. According to Darwish et al [ 116 ]’s results, high immunohistochemical nuclear positivities for ki67 and p53 in a Wilms tumor were shown. According to Nussrat, et al [ 117 ], the high-grade dysplasia of colorectal cancer showed significant positive immunohistochemical markers of Ki-67 and P53.…”
Section: Discussionmentioning
confidence: 99%